Antibiotic prescription strategies and adverse outcome for uncomplicated lower respiratory tract infections: prospective cough complication cohort (3C) study. (22nd May 2017) - Little, Paul; Stuart, Beth; Smith, Sue; Thompson, Matthew J; Knox, Kyle; van den Bruel, Ann; Lown, Mark; Moore, Michael; Mant, David
Abstract : Objective  To assess the impact on adverse outcomes of different antibiotic prescribing strategies for lower respiratory tract infections in people aged 16 years or more. Design  Prospective cohort study. Setting  UK general practice. Participants  28 883 patients with lower respiratory tract infection; symptoms, signs, and antibiotic prescribing strategies were recorded at the index consultation. Main outcome measures  The main outcomes were reconsultation with symptoms of lower respiratory tract infection in the 30 days after the index consultation, hospital admission, or death. Multivariable analysis controlled for an extensive list of variables related to the propensity to prescribe antibiotics and for clustering by doctor. Results  Of the 28 883 participants, 104 (0.4%) were referred to hospital for radiographic investigation or admission, or both on the day of the index consultation, or were admitted with cancer. Of the remaining 28 779, subsequent hospital admission or death occurred in 26/7332 (0.3%) after no antibiotic prescription, 156/17 628 (0.9%) after prescription for immediate antibiotics, and 14/3819 (0.4%) after a prescription for delayed antibiotics. Multivariable analysis documented no reduction in hospital admission and death after immediate antibiotics (multivariable risk ratio 1.06, 95% confidence interval 0.63 to 1.81, P=0.84) and a non-significant reduction with delayed antibiotics (0.81, 0.41 to 1.64, P=0.61). Reconsultation for new, worsening, or non-resolving symptoms was common (1443/7332 (19.7%), 4455/17 628 (25.3%), and 538/3819 (14.1%), respectively) and was significantly reduced by delayed antibiotics (multivariable risk ratio 0.64, 0.57 to 0.72, P<0.001) but not by immediate antibiotics (0.98, 0.90 to 1.07, P=0.66). Conclusion  Prescribing immediate antibiotics may not reduce subsequent hospital admission or death for young people and adults with uncomplicated lower respiratory tract infection, and such events are uncommon. If clinicians are considering antibiotics, a delayed prescription may be preferable since it is associated with a reduced number of reconsultations for worsening illness.